(untitled) (Conferencea, 2023)
Journal editors often rely on abstracts to decide whether or not to read a research article. While abstracts have been recognized as important in applied linguistics, they have been relatively neglected in research. This paper aims to conduct a genre analysis of research article (RA) abstracts. The paper will begin by providing an overview of the concept of genre and English for Specific Purposes (ESP) approaches to genre analysis. Following this, twelve RA abstracts from the journal Applied Linguistics will be analyzed using Pho’s (2008) model as a framework. The findings of this analysis will then be compared with existing literature on the topic and discussed in terms of their relevance to the language classroom.